The effect of non-tariff measures (NTMS) on Indonesian pulp and paper exports - Rissa Hurulaini Ramadhani Nasution (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
Non-Tariff Measures (NTMs) are likely applied by some major trading countries. The NTM policy mostly applies Sanitary and Phytosanitary (SPS) and Technical Barrier to Trade (TBT). Pulp and Paper commodities are some of Indonesia’s potential exports facing NTM barriers by a number of major destinations countries. This study is aimed to evaluate the effects of NTMs upon Indonesian pulp and paper export in the main destinations. NTMs are represented by coverage ratio of SPS and coverage ratio of TBT. The effect of NTMs imposition to pulp and paper between Indonesia and its main trade partners is estimated by using a panel data gravity model that is constructed by disaggregated data on bilateral export trade flow of pulp and paper between Indonesia and its main trade partners for the period from 2005 to 2019. The gravity model is estimated by a fixed effects model, Poisson Pseudo Maximum Likelihood, and Hausman Taylor model. The results indicated that the imposition of SPS and TBT of destination countries presented a positive and significant impact upon the Indonesian export of pulp. However, the imposition of SPS and TBT of destination countries presented a negative and significant impact upon the Indonesian export of paper.